Prevalence of Metabolic Syndrome and its Component in Patients with Acute Coronary Syndrome. - Rajbhandari, Ajay; Pandeya, Dipendra Raj; Bhattarai, Madur Dev; Malla, Ravi; Sharma, Arun; Shrestha, Dina; Chettry, Pratik (Medical Journal of Shree Birendra Hospital, 2015)
Background: Urinary tract infection (UTI) is one of the most frequently encountered problems owing tosigniÞ cant number of patients needing hospitalization during pregnancy. The incidence of UTI in pregnantwomen is reported to be high up to 7-8%. Methods: This is a prospective study conducted in Valley Maternity Hospital during a period of 6 months(Jan 2011 to June 2011). 520 MSU (Mid stream urine samples) from pregnant women clinically suspected ofurine infection were evaluated by urine dipstick analysis, microscopic and culture method. The isolates wereidentiÞ ed and antibiotic sensitivity pattern was determined by standard protocol. Results: The majority of the patients were in-between the age group of 20-30years- 338cases (65%) and thesepatients usually presented in the Þ rst trimester of pregnancy- 317cases (60.96%). Out of the 520 clinicallysuspected UTI cases, 232 (44.61%) was culture positive. Out of the culture positive cases; Escherichia coli(E.coli) was the most common accounting for a total of 144cases (80%). Nitrofurantoin was found to be the mosteffective drug against the gram negative (Gm-ve) bacteria. Similarly, Ampicillin, Amoxycillin and Cloxacillinwere found to be effective agent against gram positive (Gm+ve) bacteria.Conclusion: Screening for bacteriuria is recommended among all pregnant women at the Þ rst prenatal visit andin the subsequent trimesters of pregnancy.Key words: UTI, Pregnant women, Antibiotics, Culture method.Prevalence of Metabolic Syndrome and its Component inPatients with Acute Coronary Syndrome. Conclusions: Metabolic syndrome is most common and important risk factor in patients of coronary arterydisease. Other risk factors like smoking, obesity, dyslipidemia, hypertension and diabetes were also frequentlyfound. Public awareness to control the risk factors can reduce the prevalence of coronary artery disease in ourcountry. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12928